Investigation of keratinase activity and feather degradation ability of immobilised Bacillus sp. Khayat in the presence of heavy metals in a semi continuous fermentation - Yusuf I.; Shukor M.Y.; Syed M.A.; Yee P.L.; Shamaan N.A.; Ahmad S.A. (SPB Pharma Society, 2024)
Indexed by Scopus